ANALISIS EFISIENSI PEMASARAN IKAN BANDENG DI KECAMATAN TIRTAJAYA KABUPATEN KARAWANG - Dina Azhara; Ratna Winandi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
Karawang Regency is the center of milkfish production in West Java. Milkfish production continues to increase, but the prices fluctuate. Price fluctuations cause income uncertainty both for farmers as producers and traders as marketing agencies. Price fluctuations are closely related to marketing systems. The purpose of this study was to determine the marketing system and marketing efficiency of milkfish in Tirtajaya District, Karawang Regency. The sampling method was carried out by the snowball sampling method which started from 33 farmers. The results showed that there were 6 (six) marketing channels for milkfish in Tirtajaya District. Marketing agencies that involved are village traders, wholesalers, retailers and processors. Judging from the marketing margin value and farmer's share, all marketing channels of milkfish formed in Tirtajaya District are efficient. Marketing channel 1 more efficient relatively with the lowest margin value of 9,71 percent and the highest farmer share of 90.29 percent. The ratio of profit to cost ratio for all marketing channel is distributed evenly.